2012
DOI: 10.1117/12.931499
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tone mapping operators on visual attention deployment

Abstract: High Dynamic Range (HDR) images/videos require the use of a tone mapping operator (TMO) when visualized on Low Dynamic Range (LDR) displays. From an artistic intention point of view, TMOs are not necessarily transparent and might induce different behavior to view the content. In this paper, we investigate and quantify how TMOs modify visual attention (VA). To that end both objective and subjective tests in the form of eye-tracking experiments have been conducted on several still image content that have been pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…This fact isn't in line with subjects behavior during 2D content visualization, investigated by Narwaria et al 28 who indicate that every operator has a signature in visual attention maps. The toggling and fixation locations are thus not sufficient to investigate in depth subjects behavior, leading to the need of introducing eye gaze tracking or at least eye gaze prediction.…”
Section: Toggling and Fixation Locations Analysismentioning
confidence: 74%
See 1 more Smart Citation
“…This fact isn't in line with subjects behavior during 2D content visualization, investigated by Narwaria et al 28 who indicate that every operator has a signature in visual attention maps. The toggling and fixation locations are thus not sufficient to investigate in depth subjects behavior, leading to the need of introducing eye gaze tracking or at least eye gaze prediction.…”
Section: Toggling and Fixation Locations Analysismentioning
confidence: 74%
“…Narwaria et al 28 reviewed the criteria on which is based the differentiation of tone mapped images. The recurrent and most used criteria were selected for our questionnaire and are the following: Details in the bright areas, Details in the dark areas, Unnatural colors, Ghosting, Noise, Overall brightness, Overall contrast and Naturalness of the scene.…”
Section: Experiments Designmentioning
confidence: 99%
“…Therefore a good tone-mapping operator should retain features such as intensity contrast and visual attentionfixation points. Regarding the latter, the work in [41] presents an informative study on how tone-mapping operators influence visual attention. The tone-mapping curve presented offers finer granularity where the luma histogram is denser while coarse mapping is applied to regions where the luma values are more sparse.…”
Section: Derivation Of An Hdr Idq Profilementioning
confidence: 99%
“…Similarly, a recent study [18] of 38 participants found no significant difference among tone mapped images and a single exposure, chosen as the zero exposure, when compared with the reference HDR; this is not necessarily the best exposure to show, yet the participants still did not prefer the tone mapped images over the single exposure. There is also evidence that tone mapped images can change the visual attention of an image [19] and of the compressed content [4]. Furthermore, different tone mappers can perform better on different images/frames or even on different parts of the same image / frame as demonstrated by Banterle et al [20] whereby hybrid TMOs outperformed dedicated TMOs in participant experiments.…”
Section: Motivationmentioning
confidence: 99%